Testing the Structural Equation of Organizational Culture Modeling as a Moderator of Public Services - Dian Sudiantini; Istianingsih Sastrodiharjo; Bintang Narpati; Kardinah Indrianna Meutia (Journal of Accounting and Finance Management, 2022)
This study aims to examine the influence of Leadership Style, Strategic Orientation and Organizational Resources on Organizational Performance through Organizational Culture. This research was the first study to examine the influence of Leadership Style, Strategic Orientation and Organizational Resources on Organizational Performance through Organizational Culture conducted at Community Health Center. The model proposed in this study was carried out through structural equation modeling. Data were collected from a sample of 250 Community Health Center in DKI Jakarta Province. Data analysis was performed using SPSS 25 and SEM AMOS 24. The findings of this study provide several practical implications. First, Directors of Community Health Center are advised to take leadership training programs, such as public speaking & effective communication skill training program and coaching skill training program. Second, it requires entrepreneurship skill training program and risk management training program. Third, Directors of Community Health Center are advised to create programs to improve employee competence and increase the role of health leaders, as well as investment and adaptability to current technological developments in order to create resource efficiency and optimize the achievement of Community Health Center’s performance.